(untitled) (Horizontes de Enfermería, 2019)
Neonatology has as a fundamental basis the care of the newborn and its neonatalmaternal bond so it could be a very serious inconvenience if these ties are interrupted or affected in some way, either due to maternal child decompensation or also due to lack of Maternal expertise for the proper care and upbringing of the newborn. Therefore, this research work aims to raise awareness of the importance of neonatal care and the work of neonatology worldwide; This can be evidenced, with the rates of infant morbi-mortality which are strictly related to neonatal mortality, this research refers to the decrease in neonatal mortality in the northern region of the country and the importance of having a service of Health for the benefit of the community. This study is based on the comparison of infant mortality figures, demonstrating the significant decrease in neonatal mortality in Carchi and specifically in the city of Tulcán, finally a hypothesis was established that ensures that infant and neonatal mortality figures have been reduced in the period under investigation, observing lower infant mortality figures compared to previous years and this leaves open windows for health professionals to investigate later affirming or denying this hypothesis, highlighting that medical and nursing work is carried out with greater scientific technique for the benefit of neonatal health in the Canton Tulcán.